Framework para gestão dos benefícios do Building Information Modeling (BIM) em projetos de óleo, gás e petroquímica - Contini, Tiago Ajami (2021)
Companies and governments are increasingly adopting Building Information Modeling (BIM) as an asset management tool, regarding project to operations management. BIM is mostly adopted in architecture, engineering, and construction (AEC) projects. However, other fields, such as highway and railway projects, bridges and tunnels, ports and airports, power plants, mines, dams, oil, gas, and petrochemicals (OGP) have also benefited from its use. This work focus on the use of BIM, specifically in OGP process plants and projects. However, the management of the benefits of using BIM in some projects currently fail in several points. Thus, this research aims to answer the following question: “how to manage the benefits of BIM for managing OGP projects?”. This work consists is a qualitative research involving three stages: (1) survey of the state of art on the benefits of BIM in Project Management, through a systematic literature review (SLR); (2) proposal of a Network of Dependence on Benefits (NDB), following the theoretical approach of Benefits Management by Ward and Daniel (2006), considering interviews with practitioners and academics who work with BIM; and (3) comparison between the benefits raised in the SLR and the benefits identified in the interviews. As a result of this research, we point out the list of benefits found in the literature and the list of benefits reported by the interviewees, with the reduction of project duration, better accuracy in deliveries, greater accuracy in the budget and the reduction of rework being. The results also indicate the elaboration of NDB, including the main organizational factors that guide the adoption of BIM; and the organizational objectives that drive the adoption of BIM, which ranges from organizational objectives (increase in profit margin, increase in revenue) to the necessary changes (new work processes, new knowledge and skills, new software and new hardware).